Analisis Strategi Marketing Mix Terhadap Keputusan Mahasiswa Program Studi Pendidikan Ekonomi Memilih Kuliah pada IKIP PGRI Kalimantan Timur Samarinda - Enny Kartini; Tri Widyasari; Umi Fitria; Syarifah (Yayasan Pembina Lembaga Pendidikan (YPLP) PGRI Kabupaten Sumbawa Barat - NTB - Indonesia, 2023)
Students’ decision to enter a tertiary institution is influenced by the applied-marketing strategies, one of which is the marketing mix strategy. It uses the 7P concept: product, price, place, people, process, promotion, and physical evidence. Hereby, this study aims to measure the effect of the marketing mix strategy elements on the students’ decisions and to determine the most dominant marketing mix strategy variable in determining the student’s decision to study at the IKIP PGRI Kalimantan Timur. The population in this study was 272 students of the Economic Education Study Program, which comprised 153 people sample. Subsequently, the data analysis techniques used multiple regression analysis and hypothesis testing using the F test. The result showed a simultaneous influence between the seven marketing mix elements on the students’ decisions of economic education to study at IKIP PGRI Kalimantan Timur, in which the variable “people” is the dominant variable influencing students in making decisions and followed by the variable “process”.